Instrumen Penilaian Hasil Belajar pada Kompetensi Pengetahuan - Maharani, Rani; Urfa, Salsa Rojana; Ropidoh, Siti (Lembaga Yasin AlSys, 2023)
The accuracy of the assessments carried out by schools, especially those related to class assessments, expresses the desire for student learning outcomes. For a teacher, the use of assessment tools is very important during the evaluation process. Starting from the assessment of the selection instrument, the preparation instrument, the review instrument, the implementation of the assessment, the analysis of the results of the assessment, and the follow-up program on the results of the assessment. This article uses the library research method, namely by collecting data related to the title of the research discussion. In this study the data collected from several sources were used, including scientific journals, research results in the form of theses, and the internet. Competence is often used to indicate one's qualifications or abilities. Knowledge assessment can be called cognitive assessment, which is a process for obtaining and using knowledge possessed by students in experiencing a process of change in learning, which consists of: recognizing, remembering, creating, and understanding material. given by their teacher during learning. The main purpose of this cognitive assessment is to find out the target in measuring the level of mastery of students about the competencies that have been achieved in the knowledge aspect. Knowledge assessment is carried out using various assessment techniques The techniques commonly used are written tests, oral tests, and assignments. The learning outcomes are when a person has learned to experience a change in behavior in that person, for example from those who do not know to know, and from those who do not understand to understand. Assessment is very necessary in learning process. Assessment instruments are very important in measuring student learning outcomes. Teachers use assessment tools, which include assessment of selection instruments, preparation instruments, study instruments, implementation of assessments, analysis of assessment results, and follow-up of assessment results. Competence refers to basic knowledge, skills and values that are reflected in a person's habits of thought and action. Common assessment techniques include written tests, oral tests, and assignments.